2004
DOI: 10.1074/jbc.m400732200
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate Promotes the Growth of Tumors Derived from Human Cancer Cells in Vivo and Stimulates Proliferation in Vitro with Enhanced Cyclin-dependent Kinase-2 Activity

Abstract: Malignant cells are known to have elevated rates of mevalonate synthesis because of increased levels and catalytic efficiency of 3-hydroxy-3-methylglutaryl-CoA reductase. Whether this increased mevalonate synthesis occurs as a consequence of increased requirements for a mevalonate-derived metabolite in response to rapid growth or whether mevalonate promotes the growth of tumor cells is unknown. To address this question, we administered mevalonate via miniosmotic pumps to nude mice inoculated with MDA-MB-435 hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
67
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 61 publications
5
67
0
3
Order By: Relevance
“…WT-1 is also able to negatively regulate expression of MYB, whereas MAF can reduce MYB activity through heterodimeriziation (McCann et al, 1995;Hedge et al, 1998). In vivo and in vitro assays assessing tumor growth and cellular proliferation have demonstrated that 3-hydroxy-3-methylglutaryl coenzyme A reductase can stimulate CCNE1/CDK2 activity (Tanaka et al, 1998;Duncan et al, 2004). In contrast, ZAK, which encodes a serine/threonine kinase, is associated with reduced cyclin E1 levels and cell-cycle arrest (Yang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…WT-1 is also able to negatively regulate expression of MYB, whereas MAF can reduce MYB activity through heterodimeriziation (McCann et al, 1995;Hedge et al, 1998). In vivo and in vitro assays assessing tumor growth and cellular proliferation have demonstrated that 3-hydroxy-3-methylglutaryl coenzyme A reductase can stimulate CCNE1/CDK2 activity (Tanaka et al, 1998;Duncan et al, 2004). In contrast, ZAK, which encodes a serine/threonine kinase, is associated with reduced cyclin E1 levels and cell-cycle arrest (Yang, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hydrophilic statins have no inhibitory effect on HMG-CoA reductase activity in cells with an extrahepatic origin, while statins are involved in mevalonic acid synthesis and could potentially increase carcinogenic risk (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Although statins efficiently reduce serum cholesterol levels, recent research indicates that statins affect not only synthesis of cholesterol, but also, through inhibition of HMGR, affect other intermediates in the cholesterol pathway and, thus, may lead to many undesirable effects. In fact, it has been hypothesized that the use of pravastatin might increase the incidence of extrahepatic cancers (32,33).…”
Section: Discussionmentioning
confidence: 99%